2020
DOI: 10.1530/erc-20-0018
|View full text |Cite
|
Sign up to set email alerts
|

HEREDITARY ENDOCRINE TUMOURS: CURRENT STATE-OF-THE-ART AND RESEARCH OPPORTUNITIES: New and future perspectives for parathyroid carcinoma

Abstract: This report summarizes published data on parathyroid cancer, with the inclusion of topics discussed at MEN2019: 16th International Workshop on Multiple Endocrine Neoplasia, 27–29 March 2019, Houston, TX, USA. An expert panel on parathyroid cancer was constituted by the Steering Committee to address key questions in the field. The objectives were to recap open forum discussion of interested parties from multiple disciplines. The expert panel met in a closed session to consult on the data to be highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Application of next‐generation sequencing methods has significantly extended the landscape of genomic alterations in parathyroid carcinoma. Recent studies have suggested that genes from the PIK3CA/AKT/mTOR pathway were potentially targetable in parathyroid carcinoma 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…Application of next‐generation sequencing methods has significantly extended the landscape of genomic alterations in parathyroid carcinoma. Recent studies have suggested that genes from the PIK3CA/AKT/mTOR pathway were potentially targetable in parathyroid carcinoma 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…PC is a radioresistant tumor, and there is no indication that radiotherapy is performed as a regular treatment ( 30 ). The PC analysis in the National Cancer Data Base (NCDB) showed that radiotherapy did not improve the OS rate of patients ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib was discontinued and a second more potent antiangiogenic inhibitor, lenvatinib, was initiated. After 20 months the disease was radiographically stable, and his calcium level was well controlled without any medication ( 30 ). When well-tolerated, TKIs ensure a radiographic and hormonal control of disease, associated with normalization of calcium, at least in the medium-short term.…”
Section: Discussionmentioning
confidence: 99%